Modeling Canine Hemangiosarcoma Progression Using Patient-Derived 2.5D Organoids and Orthotopic Xenografts - Yishan Liu; Haru Yamamoto; Mohamed Elbadawy; Amira Abugomaa; Masahiro Kaneda; Yomogi Shiota; Tadashi Kondo; Tatsuya Usui; Kazuaki Sasaki (Veterinary Sciences, 2026)
Canine hemangiosarcoma (HSA) is a highly aggressive vascular malignancy encountered in veterinary practice and exhibits histopathological and molecular similarities to human angiosarcoma (AS). Despite its clinical importance, the molecular mechanisms driving canine HSA remain poorly understood, limiting the development of effective therapeutic approaches. To address this challenge, we established patient-derived canine HSA 2.5D organoids as a preclinical model. Following validation of lineage-specific marker expression, we evaluated drug responses and performed transcriptomic analyses comparing HSA organoids with nodular hyperplasia (NH) samples to identify molecular alterations associated with malignant transformation. Differential gene expression analysis revealed several genes enriched in HSA, including Phospholipase A and Acyltransferase 3 (PLAAT3), which was significantly upregulated in HSA organoids. Functional studies demonstrated that both siRNA-mediated silencing and pharmacological inhibition of PLAAT3 markedly reduced the invasive capacity of HSA organoid cells while exerting only modest effects on cell proliferation. In addition, orthotopic implantation of HSA 2.5D organoids into the spleens of immunodeficient mice generated xenograft tumors with metastatic behavior and histopathological features closely resembling those of the original canine tumors. Collectively, these results establish a canine HSA 2.5D organoid model and identify PLAAT3 as a candidate molecule associated with the invasive phenotype of canine HSA, providing a valuable platform for investigating disease biology and for future comparative studies of canine HSA and human AS.